Rancang Bagun Sistem Informasi Penentuan Harga Jual Pada UKM Gajah Nasional - Adi, Satriyo; Widodo, Arifin Puji; Sukmaaji, Anjik (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
UKM Gajah Nasional is one of the production company that produces product of household furniture in cormorant them , pots and pans .For this in determining the price of basic production is still using the basis of estimates .The price of basic production was obtained by means of the value of the use of raw materials, labor costs and overhead at about. UKM Gajah Nasional in determining the percentage mark up also use the basis of estimates , like adding a few percent of the price of basic production is based on with without calculation .This will impact to the level of sales companies and indirectly affect income received .In this study the issue resolved by developing a system of information selling price. Is targeted to the selling price plus with mark up' boarding product .So that in designing the application of the determination of the selling price to be built , need some information will be the input of the determination of the selling price .The price of basic information such as production and information and data that would be expected profit of non ( the cost of production and marketing costs ) administration .